Killing of human myelomonocytic leukemia and lymphocytic cell lines by Actinobacillus actinomycetemcomitans leukotoxin. - Simpson, D L (1988)
The purified leukotoxin of Actinobacillus actinomycetemcomitans kills human leukemic cell lines (e.g., HL-60, U937, and KG-1) and human T- and B-cell lines (e.g., JURKAT, MOLT-4, Daudi, and Raji) in a dose- and time-dependent manner. The 50% effective doses for these cell lines are similar to those established for human polymorphonuclear leukocytes and monocytes. In contrast, other human and nonhuman tumor cell lines are not susceptible to the leukotoxin. These human leukemia and lymphoid cell lines will serve as useful model systems with which to study the molecular specificity and mechanism(s) of action of the actinobacillus leukotoxin.